Epidemiology of eating disorders in Europe: prevalence, incidence, comorbidity, course, consequences, and risk factors. Issue 6 (November 2016) - Keski-Rahkonen, Anna; Mustelin, Linda
Abstract : Purpose of review: Eating disorders – anorexia nervosa, bulimia nervosa, and binge eating disorder – affect numerous Europeans. This narrative review summarizes European studies on their prevalence, incidence, comorbidity, course, consequences, and risk factors published in 2015 and the first half of 2016. Recent findings: Anorexia nervosa is reported by <1–4%, bulimia nervosa <1–2%, binge eating disorder <1–4%, and subthreshold eating disorders by 2–3% of women in Europe. Of men, 0.3–0.7% report eating disorders. Incidences of anorexia appear stable, whereas bulimia may be declining. Although the numbers of individuals receiving treatment have increased, only about one-third is detected by healthcare. Over 70% of individuals with eating disorders report comorbid disorders: anxiety disorders (>50%), mood disorders (>40%), self-harm (>20%), and substance use (>10%) are common. The long-term course of anorexia nervosa is favorable for most, but a substantial minority of eating disorder patients experience longstanding symptoms and somatic problems. The risk of suicide is elevated. Parental psychiatric disorders, prenatal maternal stress, various family factors, childhood overweight, and body dissatisfaction in adolescence increase the risk of eating disorders. Summary: Eating disorders are relatively common disorders that are often overlooked, although they are associated with high comorbidity and serious health consequences.